Participatory Evaluation of Bread Wheat (Triticum aestivum L.)Varieties for its Yield Performance at Madda Walabu District of Bale Zone, South Eastern Ethiopia - Mitiku, Ashenafi (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2019)
Wheat is the cheapest source and supplies of the calories and protein in the average diet. The study was conducted in semi arid area of Bale Zone of south eastern part of Ethiopia. The experiments were conducted as a principle of PRG approach with the objectives of to Participatory evaluation of bread wheat varieties for its yield performance at Madda Walabu District of Bale Zone. The experiments were laid out in Randomized Complete Block design (RCBD) with three replications. During the experiment the PRG group was used five types of bread wheat varieties such as Paven76, Digalu, Kakaba, Ogolcha and Local bread wheat. PRG group was evaluated the varieties based on the following wheat performance effective tiller, grain per spike, spike length, weight of grain yield are the basic wheat evaluation criteria of PRG. Statistical analysis of experiment showed that all the varieties were affected significantly P<0.05. Result shows that maximum number of tillers 6/plants, 1000 grain weight (50.33g), grain per spike (37.3), spike length (7cm), and grain yield (2746kg/ha) at maturity were recorded in Ogolcha variety followed by Kakaba, paven 76 and Digalu varieties where as the lower performance was recorded at the local bread wheat which is 2000.33kg/ha. From the result Ogolcha and Kakaba varieties were non-significant effect which are 2746 Kg/ha and 2687.67Kg/ha on their yield. Therefore, among the improved bread wheat varieties PRG was selected Ogolcha variety based on its yield and recommended to the agro ecology.